2018
DOI: 10.15741/revbio.06.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Salmonella, climatic change, Mexico, biofilms, antimicrobial resistance, genetic diversity. línea, 2) habilidad para utilizar fuentes alternas de carbono, y 3) capacidad de formar biopelículas. El uso de alguna estrategia o la combinación de ellas por las poblaciones de Salmonella circulantes podría aumentar el riesgo para la salud de la población. Por ello, esta revisión tiene como objetivo analizar de manera exhaustiva los elementos que le confieren una mayor capacidad de adaptación, favoreciendo las dinámic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In Mexico, the National Epidemiological Surveillance System (Sistema Nacional de Vigilancia Epidemiológica, SINAVE) demonstrated a considerable increase in cases of salmonellosis from 1984 to 2017 (from 31,943 to 104,471), and the state of Sinaloa had the highest rate corresponding to 12.9% of cases [49]. Although the routes of exposure to Salmonella in this agricultural region have not been well defined and are often epidemiologically unrelated to specific sources [18,20,27], several studies have suggested that surface waters in this agricultural region could potentially serve as the source of Salmonella contamination of produce. Therefore, tracing Salmonella in surface waters is of utmost importance, not only for human health, but also for the safety of the fresh produce industry in this region [18,27,50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Mexico, the National Epidemiological Surveillance System (Sistema Nacional de Vigilancia Epidemiológica, SINAVE) demonstrated a considerable increase in cases of salmonellosis from 1984 to 2017 (from 31,943 to 104,471), and the state of Sinaloa had the highest rate corresponding to 12.9% of cases [49]. Although the routes of exposure to Salmonella in this agricultural region have not been well defined and are often epidemiologically unrelated to specific sources [18,20,27], several studies have suggested that surface waters in this agricultural region could potentially serve as the source of Salmonella contamination of produce. Therefore, tracing Salmonella in surface waters is of utmost importance, not only for human health, but also for the safety of the fresh produce industry in this region [18,27,50].…”
Section: Discussionmentioning
confidence: 99%
“…Although the routes of exposure to Salmonella in this agricultural region have not been well defined and are often epidemiologically unrelated to specific sources [18,20,27], several studies have suggested that surface waters in this agricultural region could potentially serve as the source of Salmonella contamination of produce. Therefore, tracing Salmonella in surface waters is of utmost importance, not only for human health, but also for the safety of the fresh produce industry in this region [18,27,50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations